Metformin is associated with improved clinical outcomes in patients with melanoma: a retrospective, multi-institutional study - Augustin, Ryan C.; Huang, Ziyu; Ding, Fei; Zhai, Shuyan; McArdle, Jennifer; Santisi, Anthony; Davis, Michael; Sander, Cindy; Davar, Diwakar; Kirkwood, John M.; Delgoffe, Greg M.; Warner, Allison Betof; et al. (Frontiers in Oncology, 2023)
Background Pre-clinical studies have shown that metformin reduces intratumoral hypoxia, improves T-cell function, and increases sensitivity to PD-1 blockade. However, the impact of this drug in diabetic melanoma patients has not yet been fully elucidated. Methods We reviewed 4,790 patients with stage I-IV cutaneous melanoma treated at the UPMC-Hillman Cancer Center and Memorial Sloan Kettering Cancer Center between 1996-2020. The primary endpoints included recurrence rates, progression free survival (PFS), and overall survival (OS) with and without metformin exposure. Tabulated variables included BRAF mutational status, immunotherapy (IMT) by type, and incidence of brain metastases. Results The five-year incidence of recurrence in stage I/II patients was significantly reduced with metformin exposure (32.3% vs 47.7%, p=0.012). The five-year recurrence rate for stage III patients was also significantly reduced (58.3% vs 77.3%, p=0.013) in the metformin cohort. OS was numerically increased in nearly all stages exposed to metformin, though this did not reach statistical significance. The incidence of brain metastases was significantly lower in the metformin cohort (8.9% vs 14.6%, p=0.039). Conclusion This is the first study to demonstrate significantly improved clinical outcomes in diabetic melanoma patients exposed to metformin. Overall, these results provide further rationale for ongoing clinical trials studying the potential augmentation of checkpoint blockade with metformin in advanced melanoma.